The Evolution of Canadian Diplomacy towards the Israeli-Palestinian Conflict - Mackay, Derek James Benik (Université d'Ottawa | University of Ottawa, 2015)
The Israeli-Palestinian conflict continues to persist despite decades of efforts from regional actors and the international community to find a lasting peaceful solution. Canada has been connected to this issue since it played a significant role in the partitioning of Palestine. This paper explores the role that Canadian diplomacy has played in trying to resolve the Israeli-Palestinian conflict since the creation of Israel in 1948 and analyzes the reasoning behind the approaches taken. Canada has historically been viewed as an honest broker in the Middle East but more recently the Government of Canada has used rhetoric that supports a more one-sided approach to the issue. This paper will discuss the impact of current Canadian diplomacy towards Israel and Palestine, as well as if the diplomatic tools Canada is equipped with can be used in ultimately helping to resolve the conflict.